The Effect of Different Polishing Methods and Storage Media on Discoloration of Resin Composites - Deljoo Z; Sadeghi M; Azar MR; Bagheri R (Shiraz University of Medical Sciences, 2016)
Statement of Problem: Accumulation of plaque and staining due to a rough surface, and penetration of colourant agents from food and beverages in to the resin composite results in an incomplete polymerization. There is a little information on the effect of finishing and polishing techniques on the discoloration of nanohybrid and microhybrid composites when exposed to staining solutions. Objectives: To determine the degree of surface staining of nanohybrid and microhybrid composites after polishing and immersion in distilled water and two commonly used staining solutions. Materials and Methods: A nanohybrid (Ice; SDI) and microhybrid (Gradis direct; GC) composites were used. Disc-shaped specimens were prepared and treated with either a matrix finish or polished using Sof-Lex discs (3M/ ESPE) and Enhance point (Dentsply). After 24 h immersion in distilled water at 37°C the specimens were polished and colour coefficients (CIE L* a* b*) was measured by a spectrophotometer. All specimens were immersed in 37°C distilled water in an incubator for 7 days and colour coefficients were measured again. The colour change (ΔE) was calculated using the following formula: ΔE = [(Δa)2+(Δb)2+(ΔL)2] 1/2. The data were analyzed using three-way ANOVA, one-way ANOVA/Tukey HSD and Student's t-test. Results: There was a significant interaction between resin composites, polishing systems and staining solutions (p < 0. 05). ANOVA and Tukey's tests showed that Ice had a significantly lesser colour change than Gradia direct and matrix finish revealed the smoothest surface followed by Sof-Lex discs and Enhance point. Distilled water and cola caused no perceptible colour change (ΔE < 3.3). The effect of surface polish on staining was statistically significant (p < 0 .05). Conclusions: Sof-Lex discs in comparison to Enhance point stimulated greater staining resistance for both composites. The nanohybrid exhibited less colour change than microhybrid composite. Coffee was the only storage media that induced a perceptible colour change (ΔE > 3.3) compared to cola and distilled water.